Acute outcome after a single cryoballoon ablation: Comparison between Arctic Front Advance and Arctic Front Advance PRO - Moltrasio M.; Sicuso R.; Fassini G. M.; Riva S. I.; Tundo F.; Dello Russo A.; Casella M.; Majocchi B.; Zucchetti M.; Cellucci S.; Tondo C. (Pacing and Clinical Electrophysiology, 2019)
Background: The novel fourth-generation cryoballoon (CB4) potentially allows for enhanced catheter maneuverability and more frequent capture of pulmonary vein (PV) potentials which can be used to monitor real-time PV isolation (PVI). The aim of our study is to compare the acute procedural endpoints between the CB4 and second-generation cryoballoon (CB2). Methods: A single-center retrospective chart review was used to examine 50 consecutive patients with drug-refractory atrial fibrillation undergoing CB4-based PVI. Procedural data and acute success of these patients were compared to 50 propensity-matched controls who underwent cryoballoon ablation procedure using CB2. Results: Procedures performed with the CB4 showed significant shorter fluoroscopy time (14.8 ± 5.5 vs 18.0 ± 6.5 minutes, P =.04), shorter procedure time (58.3 ± 15.7 vs 65.3 ± 21 minutes, P =.13), and shorter total ablation time (10.8 ± 1.5 vs 13.8 ± 1.9 minutes, P =.42). The real-time PVI visualization rate was 33.3% in the CB2 group and 74.7% in the CB4 group (P <.001). CB4 was correlated to significant increase of acute real-time recordings with regard to all the single PV (left superior PV: 58% vs 84%, P =.02; left inferior PV: 26% vs 71%, P =.001; right superior PV 29% vs 61%, P =.01; and right inferior PV 19% vs 58%, P =.002). Conclusion: The CB4 was more often able to capture real-time recordings of PV potentials and the subsequent acute PV isolation.